ANALISIS PELAKSANAAN PELAYANAN PUBLIK DI KANTOR CAMAT TAPALANG KABUPATEN MAMUJU - Muhammad Massyat (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2017)
This study aims to determine how far the implementation of public services was held at Tapalang Mamuju District Head Office, by referring to good governance standards. The types of services available are; the field of government consists of the services of KTP and KK; the field of development consists of IMB services and land warfare letters; general field is the service of certificate of heirs, birth certificate, and death certificate. In this study, the author uses descriptive research type. The sample selection was used purposive sampling technique. The results showed that the behavior of the apparatus regarding obedience, perseverance, satisfaction was quite high, discipline was still low, responsibility was still low, the quality of IMB and SITU procedures were difficult, KTP and KK services were quite easy, permit services were quite easy.